2019
DOI: 10.25518/0037-9565.8822
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic activities on active solar-type stars

Abstract: Indian Institute of Astrophysics, II Block Koramangala, Bangalore 560034, India We present results obtained from the studies of magnetic activities on four solar-type stars (F-type star KIC 6791060, K-type star LO Peg, and two M-type planet-hosting stars K2–33 and EPIC 211901114) by using optical observations from several ground- and space-based telescopes. In this study, we investigate magnetic activities such as spot-topographic evolution and flaring events in these stars. We compare the results obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Low mass stars with partially or fully convective envelops show a high level of magnetic activities (see Pandey & Karmakar, 2015;Patel et al, 2016;Savanov et al, 2016Savanov et al, , 2019Karmakar, 2019Karmakar, , 2021Karmakar et al, 2016Karmakar et al, , 2017Karmakar et al, , 2022Karmakar et al, , 2023. Recent studies have shown the magnetic activities also increase for the later spectral types (e.g., Savanov et al, 2018;Karmakar et al, 2019). Typically, the stars with a mass range of 0.075-0.6 M are called very low mass stars (VLMs).…”
Section: Introductionmentioning
confidence: 99%
“…Low mass stars with partially or fully convective envelops show a high level of magnetic activities (see Pandey & Karmakar, 2015;Patel et al, 2016;Savanov et al, 2016Savanov et al, , 2019Karmakar, 2019Karmakar, , 2021Karmakar et al, 2016Karmakar et al, , 2017Karmakar et al, , 2022Karmakar et al, , 2023. Recent studies have shown the magnetic activities also increase for the later spectral types (e.g., Savanov et al, 2018;Karmakar et al, 2019). Typically, the stars with a mass range of 0.075-0.6 M are called very low mass stars (VLMs).…”
Section: Introductionmentioning
confidence: 99%